2023
DOI: 10.1109/tnsre.2023.3339768
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation Phenomenon Emerged During Prolonged Fatigue Driving: An EEG Connectivity Study

Gang Li,
Jie Wang,
Wanxiu Xu
et al.

Abstract: Driving fatigue is a common experience for most drivers and can reduce human cognition and judgment abilities. Previous studies have exhibited a phenomenon of the nonmonotonically varying indicators (both behavioral and neurophysiological) for driving fatigue evaluation but paid little attention to this phenomenon. Herein, we propose a hypothesis that the non-monotonically varying phenomenon is caused by the self-regulation of brain activity, which is defined as the fatigue self-regulation (FSR) phenomenon. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…[ 36 ], our study aimed to assess mental fatigue, only focusing on experimental factors and thus excluding non-fatigue-related operations. From this standpoint, by exclusively estimating significant connections that exhibit an increasing or decreasing trend over the entire duration, we can avoid incorporating fatigue characteristics that could be internally regulated [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 36 ], our study aimed to assess mental fatigue, only focusing on experimental factors and thus excluding non-fatigue-related operations. From this standpoint, by exclusively estimating significant connections that exhibit an increasing or decreasing trend over the entire duration, we can avoid incorporating fatigue characteristics that could be internally regulated [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although self-perceived assessment usually fails to overcome subjective perception concerning the individuality of the subjects [ 8 ], utilizing physiological measures can provide insights into the actual impact of mental fatigue on cognitive functioning, independently of individuals’ subjective perceptions [ 9 ]. In fact, cortical variability in states of fatigue is well-documented across multiple studies, demonstrating significant differences in how individuals’ brain activity changes in response to fatigue [ 10 , 11 ]. In this regard, Lim et al [ 12 ] found that individuals exhibit considerable variability in specific EEG brain waves, presenting differentiations in power during prolonged cognitive tasks, with some showing rapid onset of fatigue indicators and others maintaining stable EEG patterns over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation